Magneto-Elastic Coupling in a Sinusoidal Modulated Magnet Cr2GaN. (1st August 2022) - Mao 毛, Hui-Can 慧灿; Li 李, Yu-Feng 玉峰; Ren 任, Qing-Yong 清勇; Chu 褚, Mi-Hai 密海; Maynard-Casely, Helen E.; Demmel, Franz; Adroja, Devashibhai; Wen 闻, Hai-Hu 海虎; Xiao 肖, Yin-Guo 荫果; Luo 罗, Hui-Qian 会仟
Abstract : We use neutron powder diffraction to investigate the magnetic and crystalline structure of Cr2 GaN. A magnetic phase transition is identified at T ≈ 170 K, whereas no trace of structural transition is observed down to 6 K. Combining Rietveld refinement with irreducible representations, the spin configuration of Cr ions in Cr2 GaN is depicted as an incommensurate sinusoidal modulated structure characterized by a propagating vector k = (0.365, 0.365, 0). Upon warming up to the paramagnetic state, the magnetic order parameter closely resembles to the temperature dependence of c -axis lattice parameter, suggesting strong magneto-elastic coupling in this compound. Therefore, Cr2 GaN provides a potential platform for exploration of magnetically tuned properties such as magnetoelectric, magnetostrictive and magnetocaloric effects, as well as their applications.